Protective effect of allograft inflammatory factor-1 on the apoptosis of fibroblast-like synoviocytes in patients with rheumatic arthritis induced by nitro oxide donor sodium nitroprusside. (October 2013) - Liu, Y; Mei, C; Du, R; Shen, L
Abstract : Objectives: Inadequate apoptosis of rheumatic arthritis (RA) fibroblast-like synoviocytes (FLS) plays a crucial role in the immunopathogenesis of RA. Allograft inflammatory factor-1 (AIF-1) is a novel member of the cytokine network that has been found to be involved in the immunological process underlying RA. This study was undertaken to investigate the potential effects of AIF-1 on nitric oxide donor (NO) sodium nitroprusside (SNP)-induced RA-FLS apoptosis, and the possible molecular mechanisms underlying these effects. Method: FLS obtained from patients with active RA were cultured in vitro and treated with SNP in the present or absence of AIF-1. RA-FLS viability was tested by the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-tetrazolium bromide (MTT) assay. RA-FLS apoptosis was analysed by flow cytometry and terminal dUTP nick-end labeling (TUNEL). The levels of phospho-Akt (p-Akt) and phospho-BAD (p-BAD) protein were detected by Western blot. Results: A 24-h AIF-1 pretreatment at concentrations ranging from 10 to 100 ng/mL increased the viability of RA-FLS and prevented RA-FLS apoptosis in a dose-dependent manner in the presence of SNP. AIF-1 induced phosphorylation of Akt and BAD in a time- and concentration-dependent manner. The effect was reversed by treatment with the PI3K inhibitor LY2940042 (LY) and the nuclear factor kappa B (NF-κB) inhibitor pyrrolidine dithiocarbamate (PDTC). Conclusions: AIF-1 can protect RA-FLS from apoptosis induced by NO by upregulating the expression of p-Akt and p-BAD.